A scheme for more efficient usage of CALPHAD data in simulations. (September 2015) - Larsson, Henrik; Höglund, Lars
Abstract: A method is suggested that allows thermodynamic data to be dynamically stored and retrieved. The purpose of the method is to reduce computer simulation time when Calphad type databases are being used. Some test simulations are presented and these indicate that simulations can be made to run 5–40 times faster without any significant loss of accuracy. Abstract : Highlights: A method that can increase the speed of simulations is suggested. Examples show 5–40 times speed increase. No significant loss of accuracy.